Inner Worlds of Characters with Mental Illness in Children’s and YA Literature - KUZMINYKH, Ksenia (Anafora, 2023)
The paper discusses manifestations of emotions within illness narratives in children’s and YA literature. It starts with a short historical and theoretical overview, which presupposes that emotions are intersubjective and culturally determined phenomena. The expression of emotions takes place on all linguistic levels, and can therefore be both explicit and implicit. The theoretical and historical overview is followed by a literary analysis of illness narratives and emotions of ill characters in children’s and YA literature. Finally, by employing the research method of close reading, the article offers a typology of explicit and implicit emotions in the selected illness narratives for children and YA readers. The selection of texts is based on their exemplary character for the explication of emotions of the ill characters.